About a non-existent right. On «Democracy and the right to decide» by Josep M. Vilajosana - Atienza Rodríguez, Manuel (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The author considers that the thesis defended in the work of J. M. Vilajosana, Democracia y derecho a decidir, is untenable: the right to decide (that is, the right to secession) is incompatible with current Spanish law. Among many other defects, Vilajosana’s thesis presupposes a conception of law and interpretation in which the text of the norms (specifically that of the constitutional norms) is completely irrelevant.